Sand chronicles. Vol. 9 - Ashihara, Hinako (Viz Media ; Simon & Schuster [distributor, 2010)
"What were our parents like at our age? We'll never really know ... But now you can get a glimpse into the teenage years of the mothers of Ann, Daigo, Fuji and Shika. How was their destiny shaped? Plus, Ann's little sister visits Shika--and Ann's ex-fiancé!--in New York City."--Amazon.com.